3D- Seismic Analysis of Paleocene Carbonate Succession in Nafoora Area, Southeast Sirt Basin, Libya - El-Shari , Saad M. (Scientific Journal of University of Benghazi, 2021)
This paper focuses on seismic interpretation of Paleocene sequence in Nafoora area. Composite logs, check shots and sonic logs for many wells in the block 51W have been used herein. The paper aimed to i) present time structural maps for each unit to demonstrate their lateral distribution throughout the area of study, ii) and to evaluate the relation between the stratigraphy and structural setting across the Nafoora Fault. The maps are generated for Arish and Harach horizons on basis of 3D seismic data, and formation tops. Variations in lithology, and the development of faults, which introduce discontinuities in the reflectors mostly control the continuity of the seismic events. The fault patterns show that most of faults are of normal type with a NW-SE strike trend, these faults generally coincide with the major regional structural features in the eastern Sirt Basin. However, this study provides an opportunity to examine deposition and the stratigraphy of the carbonate platform on the southern margin of Tethys during the Paleocene. Furthermore, the work may have economic benefits to the petroleum industry in form of a predictive tool for future locations of hydrocarbon prospectivity.